Sistem Monitoring Sensor Udara Berbasis Arduino dengan Menggunakan Telegram - Visal Mohammad Rizki; Agus Herwanto; Budi Tjahjono; Bambang Irawan (Jurnal Informatika Universitas Pamulang, 2025)
This study aims to design and implement an Arduino Uno and NodeMCU ESP8266-based air quality monitoring system integrated with Telegram as an Internet of Things (IoT)-based automatic notification medium. This system uses MQ-7, MQ-135, and MG811 sensors to detect CO, CO₂, and other air pollutants. The research method is descriptive quantitative with testing at two locations with different activity levels, namely (1) Lebak Bulus Terminal (heavy traffic) and (2) Jl. H. Midar Pondok Pinang (low activity). The results show that CO levels reached 120 PPM at Lebak Bulus Terminal in the afternoon, which is categorized as “unhealthy” based on the Air Pollutant Standard Index (ISPU). The system was able to detect differences between clean and polluted air with 97% accuracy, a response time of 2.3 seconds, and a 98% notification success rate via Telegram. These results indicate that the system operates in real-time, efficiently, and is easily accessible, while also increasing public awareness of air quality and mitigating health risks due to pollution.